Negotiating A Change: Literacy Awareness: - Ruly Ningsih; Rindiani Rindiani; Dika Tri Saputra; Nanda Erviana Istiqomah; Berliana Latifa Khoirunnisa; Vinka Rahmawati; Ika Nur Arifah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Cultivating literacy awareness is an important work for schools to support the achievement of Program for International Student Assessment (PISA) in Indonesia. One way to cultivate a culture is to build a reading habit. This work aimed to increase literacy awareness among student related to School Literacy Movement (SLM). The activity conducted on March 1, 2022,until June 23, 2022, through Kampus Mengajar program. All student from first grade until fifth grade participating on that program. Literacy awareness deliver through 15 minutes each day (before class) read a book, storytelling the content of book, and literacy award to student. Kampus Mengajar agents being facilitator on that movement. The impact of the program was increased student participation in reading the books. Student frequently swapped books to the library cause finished reading.